Inovasi teknologi produk Zingiber Sugar efektif meningkatkan kesejahteraan kelompok petani nira di Kulon Progo - Pratiwi, Kurniasari; Sari, Eni Kartika; Muslim, Muhammad (ABDIMAS DEWANTARA, 2025)
Program PKM bertujuan memberikan pelatihan proses produksi nira menjadi produk gula kelapa dengan inovasi tambahan rempah jahe dan serai yang kaya manfaat yang dikemas praktis dengan brand Zingiber Sugar, pelatihan proses pemasaran dengan e-commerse dan pelatihan diversifikasi produk nira untuk meningkatkan kesejahteraan petani nira. Metode pelaksanaan program yaitu dengan inovasi produksi gula jawa (inovasi bentuk dan rasa), pemberian hibah mesin kristalisasi gula dan peralatan produksi, pelatihan pengemasan secara modern dengan standing pouch dan pelatihan pemasaran menggunakan e-commerce. PKM berjalan lancar, mitra berperan aktif dalam pelaksanaan program. Selain itu keterampilan mitra dalam pengolahan inovasi gula kelapa meningkat. Program PKM berhasil meningkatkan kesejahteraan petani nira, dibuktikan dengan pendapatan mitra meningkat dua kali lipat dibandingkan dengan harga gula sebelum adanya program. Selain itu konsumen gula meluas keseluruh Indonesia.   Zingiber Sugar product technology innovation effectively improves the welfare of nira farmer groups in Kulon Progo   Abstract: The PKM program aims to provide training in the palm sap production process into coconut sugar products with the innovation of additional ginger and lemongrass spices that are rich in benefits that are practically packaged with the brand Zingiber Sugar, training in the marketing process with e-commerce and training in the diversification of palm sap products to improve the welfare of palm sap farmers. The method of implementing the program is through innovation in the production of Javanese sugar (innovation in shape and taste), providing grants for sugar crystallization machines and production equipment, modern packaging training with standing pouches, and marketing training using e-commerce. PKM runs smoothly, partners play an active role in implementing the program. In addition, the skills of partners in processing coconut sugar innovations have increased. The PKM program has succeeded in improving the welfare of palm sugar farmers, as evidenced by the partner's income increasing twofold compared to the price of sugar before the program. In addition, sugar consumers are expanding throughout Indonesia.